A systematic review of study results reported for the evaluation of robotic rollators from the perspective of users - Werner, Christian; Ullrich, Phoebe; Bauer, Jürgen M.; Hauer, Klaus (Disability and rehabilitation. Assistive technology, 2018)
Purpose: To evaluate the effectiveness and perception of robotic rollators (RRs) from the perspective of users.Methods: Studies identified in a previous systematic review published on 2016 on the methodology of studies evaluating RRs by the user perspective were re-screened for eligibility based on the following inclusion criteria: evaluation of the human-robot interaction from the user perspective, use of standardized outcome measurements, and quantitative presentation of study results.Results: Seventeen studies were eligible for inclusion. Due to the clinical and methodological heterogeneity across studies, a narrative synthesis of study results was conducted. We found conflicting results concerning the effectiveness of the robotic functionalities of the RRs. Only a few studies reported superior user performance or reduced physical demands with the RRs compared to unassisted conditions or conventional assistive mobility devices; however, without providing statistical evidence. The user perception of the RRs was found to be generally positive.Conclusions: There is still no sufficient evidence on the effectiveness of RRs from the user perspective. More well-designed, high-quality studies with adequate study populations, larger sample sizes, appropriate assessment strategies with outcomes specifically tailored to the robotic functionalities, and statistical analyses of results are required to evaluate RRs at a higher level of evidence.Implications for RehabilitationRRs cover intelligent functionalities that focus on gait assistance, obstacle avoidance, navigation assistance, sit-to-stand transfer, body weight support or fall prevention.The evaluation from the user perspective is essential to ensure that RRs effectively address users’ needs, requirements and preferences.The evidence on the effectiveness of RRs is severely hampered by the low methodological quality of most of the available studies.RRs seem generally to be perceived as positive by the users.There is very limited evidence on the effectiveness and benefits of RRs compared to conventional assistive mobility devices.Further research with high methodological quality needs to be conducted to reach more robust conclusions about the effectiveness of RRs.
Published online: 26 Jan 2017
Gesehen am 27.11.2018